SPECIFICITY OF JUMPING, ACCELERATION AND QUICK CHANGE OF DIRECTION MOTOR ABILITIES IN SOCCER PLAYERS (Kinesiology, 2017)
The purpose of this study was to determine the underlying structure of the stretch-shortening cycle (SSC)jumping, acceleration and change-of-direction (COD) abilities in soccer players using principal componentfactor analysis (PCA). Based on the results of recent studies on male college athletes, we hypothesized thatslow SSC jumping, acceleration and COD represent independent motor abilities in soccer players. Fortytwo soccer players (23.2±2.36 yr) performed three tests for each group of rapid lower-body movements:a) three vertical slow SSC jumping tests ‒ squat jump (SJ), countermovement jump (CMJ) and arm swingcountermovement jump (CMJAS), b) three acceleration tests ‒ 5, 10 and 15 meter sprint times (ACC5,ACC10 and ACC15), and c) three COD tests ‒ modified agility test free (MATF), the 505 agility test (505)and 20 yard agility test (Y20). PCA was applied to establish the relationships among the factors (i.e. motorabilities) underlying the included manifest variables (i.e. performance tests). This procedure reduced allvariables to a smaller number of independent latent dimensions. The results indicated three separate factorsthat may correspond to slow SSC jumping, acceleration and COD abilities. The magnitude of the correlationcoefficients among the three motor abilities extracted was r